Using Event Management Systems to Block Attacks on Network - Albarghathi Mohammed Adrees Abdullah; Fediushyn, O. I. (ХНУРЕ, 2019)
A comparative analysis of the characteristics of modern event management systems to block attacks on networks was performed. The comparison this system was performed on the following indicators: monitoring and audit level, response type, adaptive capacity, architecture, detection method supported for platform deployment, principle of construction, method of extending functionality
Keywords: security information and event management; network security; log management; IDS